Combined application of DTI and BOLD-MRI in the assessment of renal injury with hyperuricemia. - Cheng, Zhong-Yuan; Lin, Qi-Ting; Chen, Ping-Kang; Si-Tu, Ding-Kun; Qian, Long; Feng, You-Zhen; Cai, Xiang-Ran (Abdominal Radiology, 2021)
Objective: To explore the value of combined diffusion tensor imaging (DTI) and blood oxygenation level-dependent magnetic resonance imaging (BOLD-MRI) in detecting early renal alterations in patients with hyperuricemia. Materials and methods: Seventy-one individuals were enrolled in this study and divided into three groups according to their serum uric acid (SUA) level and clinical symptoms: healthy controls (HC, n = 23), asymptomatic hyperuricemia (AH, n = 22) and gouty arthritis (GA, n = 26). All patients underwent both DTI and BOLD-MRI examination. Renal cortical and medullary ADC, FA and R2* values were calculated, respectively, and compared among the three groups. Correlations between ADC, FA and R2* with estimated glomerular filtration rate (eGFR) and SUA in hyperuricemia were evaluated, respectively. Result: In the renal cortex, the ADC, FA and R2* values of the AH and GA groups were significantly lower than those of the HC groups (p < 0.05). In the renal medulla, the ADC and FA values in AH and GA patients were significantly lower than those in healthy controls (p < 0.05). The R2* value of the GA group significantly decreased, compared to that of the AH and HC groups (p < 0.05). SUA was negatively correlated with cortical ADC, FA and R2* values (p < 0.05) as well as with medullary ADC and FA values. No significant correlation was discovered between the eGFR and ADC, FA and R2* values. Conclusion: The combined evaluation of DTI and BOLD might provide a sensitive and non-invasive approach for detection of renal microstructural alterations and oxygen metabolism abnormality in hyperuricemia.